Triggering and modulation of a complex behavior by a single peptidergic command neuron in Drosophila. - Fernandez-Acosta, M.; Zanini, R.; Heredia, F.; A Volonté, Y.; Menezes, J.; Prüger, K.; Ibarra, J.; Arana, M.; Pérez, M.S.; Veenstra, J.A.; Wegener, C.; Gontijo, A.M.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
At the end of their growth phase, Drosophila larvae remodel their bodies, glue themselves to a substrate, and harden their cuticle in preparation for metamorphosis. This process-termed pupariation-is triggered by a surge in the hormone ecdysone. Substrate attachment is achieved by a pupariation subprogram called glue expulsion and spreading behavior (GSB). An epidermis-to-CNS Dilp8-Lgr3 relaxin signaling event that occurs downstream of ecdysone is critical for unlocking progression of the pupariation motor program toward GSB, but the factors and circuits acting downstream of Lgr3 signaling remain unknown. Here, using cell-type-specific RNA interference and behavioral monitoring, we identify Myoinhibiting peptide (Mip) as a neuromodulator of multiple GSB action components, such as tetanic contraction, peristaltic contraction alternation, and head-waving. Mip is required in a pair of brain descending neurons, which act temporally downstream of Dilp8-Lgr3 signaling. Mip modulates GSB via ventral nerve cord neurons expressing its conserved receptor, sex peptide receptor (SPR). Silencing of Mip descending neurons by hyperpolarization completely abrogates GSB, while their optogenetic activation at a restricted competence time window triggers GSB-like behavior. Hence, Mip descending neurons have at least two functions: to act as GSB command neurons and to secrete Mip to modulate GSB action components. Our results provide insight into conserved aspects of Mip-SPR signaling in animals, reveal the complexity of GSB control, and contribute to the understanding of how multistep innate behaviors are coordinated in time and with other developmental processes through command neurons and neuropeptidergic signaling.